Thermal gelation modeling of a pluronic‐alginate blend following coronary angioplasty. Issue 25 (11th October 2019) - Milocco, Alessio; Scuor, Nicola; Lughi, Vanni; Lamberti, Gaetano; Barba, Anna Angela; Divittorio, Rosario; Grassi, Gabriele; Perkan, Andrea; Grassi, Mario; Abrami, Michela
ABSTRACT: To overcome the complications connected to the treatment of coronary atherosclerosis by means of percutaneous transluminal angioplasty followed by stent implantation, the in situ release of antiproliferative nucleic acid based drugs (NABD) seems a promising approach. For their fragile nature, NABD cannot be released from drug eluting stents but they need to be embedded in a soft gel coating the coronary wall (endoluminal gel paving). This article deals with the thermal fate, once in the catheter, of a polymer blend composed by pluronic, giving rise to a soft gel in water upon temperature rise, and alginate, a natural polysaccharide giving origin to a strong gel in the presence of divalent cations. Simulations reveal that while the formation of a pregel is rapidly achieved, the formation of a mature gel takes a much longer time with respect to the residence time of the polymer blend inside the catheter. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48539. Abstract :